2012
DOI: 10.1242/jeb.066969
|View full text |Cite
|
Sign up to set email alerts
|

Insulin signalling in mushroom body neurons regulates feeding behaviour inDrosophilalarvae

Abstract: SUMMARYWhereas the pivotal role of insulin signalling in cell division, growth and differentiation is well documented, its role in the regulation of neuronal function and behaviour has recently become the focus of intense investigation. The simple organization of the Drosophila larval brain and the availability of genetic tools to impair the function of insulin receptor signalling in a spatially specific manner makes Drosophila an attractive model to investigate the role of the insulin pathway in specific beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 69 publications
(84 reference statements)
4
29
0
Order By: Relevance
“…Since DAMB signalling in MB neurons stimulates energy metabolism, it is therefore likely that the increased feeding behaviour following spaced training is a direct consequence of the upregulation of energy metabolism in MB neurons. It was shown that in Drosophila larvae, feeding behaviour is regulated by insulin signalling on MB neurons and synaptic output from MB neurons59. The present study suggests that this property may be extended to adult Drosophila as well.…”
Section: Discussionsupporting
confidence: 64%
“…Since DAMB signalling in MB neurons stimulates energy metabolism, it is therefore likely that the increased feeding behaviour following spaced training is a direct consequence of the upregulation of energy metabolism in MB neurons. It was shown that in Drosophila larvae, feeding behaviour is regulated by insulin signalling on MB neurons and synaptic output from MB neurons59. The present study suggests that this property may be extended to adult Drosophila as well.…”
Section: Discussionsupporting
confidence: 64%
“…( D ) The heatmap demonstrates coexpression of DamGATAe (red box) with its putative target genes, although DamGATAe itself is not significantly differentially expressed. References to known interactions: 1) Honegger et al (2008) (fruit fly); 2) Huang et al (2015) (fruit fly); 3) Hwang et al (2000) (fruit fly); 4) Buch et al (2008) (fruit fly); 5) Ida et al (2011) (fruit fly); Maeda et al (2015) (blowfly); 6) Reiher et al (2011) (fruit fly); 7) Britton et al (2002) (fruit fly); 8) Veenstra (2015) (crayfish); 9) Veenstra et al (2008) (fruit fly); Fu et al (2007) (crab); 10) Chen et al (2014) (crab); 11) Lorenz et al (1995) (cricket); 12) Hua et al (1999); Davis (2003); Yamanaka et al (2010) (moths); 13) Okumura et al (2007) (fruit fly); 14) Kataoka et al (1989) (moth); 15) Kaneko and Hiruma (2015) (moth); 16) Verlinden et al (2015) (insects); 17) Natzle et al (1988) (fruit fly); 18) Nijhout et al (2014) (insects); 19) Mirth et al (2014) (insects); 20) Kethidi et al (2005) (fruit fly); 21) Zhao and Campos (2012) (fruit fly).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to conserved molecular machinery, convergence in function of this signaling pathway is also evident. During neural development, insulin signals play an important role in synapse formation, neural stem cell regulation and neuronal growth (Zhao and Campos 2012; Cheetham and Brand 2013; Scolnick et al 2008; Hung et al 2013). We have highlighted both transcription-independent and transcription-dependent actions of insulin regulating neuronal function in invertebrate and vertebrate animals.…”
Section: Discussionmentioning
confidence: 99%
“…During development, a small cluster of median neurosecretory cells release insulin into the circulatory system in response to nutrients (Ikeya et al 2002). Circulating insulin acts on neurons in the mushroom body and regulates the feeding behavior and growth of the fly larvae (Zhao and Campos 2012). In this context, the source and identity of dILPs acting on the mushroom body remains unclear.…”
Section: Insulin Signaling In the Fruit Fly D Melanogastermentioning
confidence: 99%